Some Current Trends and Research Possibilities in the Audiovisual Translation of the 2020s - Adriána Hrabčáková (Language, Culture, Politics)
This overview article explores some of the current trends and research possibilities in audiovisual translation which is a rapidly growing field of translation studies due to the increased demand for audiovisual content in the era of technology. It briefly describes audience-oriented studies and research possibilities regarding humour perception and eye tracking with a special focus on making audiovisual content available to hearing and visually impaired audience. Moreover, it outlines collaborative translation and crowdsourcing along with fansubbing and fandubbing as a popular forms of non-professional practice. The article also discusses the employment of the machine, neural machine and speech translation to audiovisual or media content.